2015
DOI: 10.1007/s00586-015-4123-7
|View full text |Cite
|
Sign up to set email alerts
|

Selection of distal fusion level in posterior instrumentation and fusion of Scheuermann kyphosis: is fusion to sagittal stable vertebra necessary?

Abstract: Proper selection of distal fusion level is important in order to prevent DJK after SK surgery. According to this study, it is not necessary to extend the fusion down to the SSV. Fusion to FLV is sufficient and saves a level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 15 publications
(44 reference statements)
2
28
2
1
Order By: Relevance
“…6 Another criticism of the study by Cho et al 4 is that they did not include a group in which the LIV and the FLD were the same level. 8 Our article includes patients in whom the LIV and FLD correspond to the same level and confirms the findings of Cho et al 4 with current-day instrumentation techniques and a larger patient cohort.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…6 Another criticism of the study by Cho et al 4 is that they did not include a group in which the LIV and the FLD were the same level. 8 Our article includes patients in whom the LIV and FLD correspond to the same level and confirms the findings of Cho et al 4 with current-day instrumentation techniques and a larger patient cohort.…”
Section: Discussionsupporting
confidence: 87%
“…Although only 44 patients were included, this is more than 4,7,9 or similar to 8 prior studies. Another weakness is our average follow-up of only 3.1 years.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Lonner et al 16 found no significant difference for development of DJK between patients fused to SSV and those fused to the FLV. Yanik et al 25 found that extension of instrumentation and fusion into the SSV are unnecessary and fusion to the FLV was sufficient and results in comparable rates of DJK and saves more mobile levels.…”
Section: Journalmentioning
confidence: 99%
“…Others recommended fusing short of the SSV and including the first lordotic disc and fusing into the first lordotic vertebra (FLV) which is just caudal to the first lordotic disc to save at least one mobile segment. 2,4,6,16,25 Few studies used the vertebra just proximal or cephalic to the first lordotic disc. 13 In this prospective study, we used the vertebra just cephalic to the first lordotic disc (FLV-1) as the LIV to save more motion segments in the lumber spine and show the results and whether this was associated with increased incidence of DJK or revision surgery.…”
Section: Introductionmentioning
confidence: 99%